The influence of herbicide protection on the yield of annual sunflower (Helianthus annuus L.) in the conditions of Western Forest Steppe - Mostoviak, I.; Krykunov, I.; Shuvar, A.; Senyk, I.; Sydoruk , H. (Quarantine and plant protection, 2024)
Methods. Field, quantitative to determine weediness of crops, mathematical and statistical to assess the reliability of the data obtained. Results. It was established that the species composition of the dicot segetal vegetation in the sunflower agrocenosis was mainly represented by white quinoa (Chenopodium album L.), common bittersweet (Amaranthus retroflexus L.), birch mustard (Polygonum convolvulus L.), field mustard (Sinapis arvensis L.). Among the variants of the experiment, the highest number of weeds was noted in the control without herbicides — 31.2 weeds/ m2. The introduction of soil and insurance herbicides contributed to the reduction of weediness of sunflower crops. The negative influence of segetal vegetation on the formation of the yield of the studied crop has been proven, which manifested itself in a decrease of its seed productivity with an increase in the number of weeds in the crops. Thus, in the control variant without the use of herbicides the yield of sunflower was the lowest and amounted to 1.55 t/ ha due to strong weediness of the crops. The highest yield of sunflower (4.13 t/ ha) was noted for the variant in which the herbicide Oscar Premium, s.e. was applied to the seedlings. at the rate of 3.75 l/ ha and post-emergence spraying of crops with a tank mixture of herbicides Challenge, s.c., 1.0 l/ ha and Heliantex, s.c., 0.045 l/ ha with the addition of Vivolt surfactant 0.25 l/ ha. Conclusions. The lowest weediness of sunflower agrocenoses (1.5 units/ m2) at the time of harvesting was noted on the variant with the use of ground (Oscar Premium, s.e. 3.75 l/ ha) and tank mixture of insurance herbicides (Challenge, s.c., 1.0 l/ ha + Heliantex, s.c., 0.045 l/ ha + Vivolt surfactant 0.25 l/ ha) in the phase of BBCH 14. The highest yield of the researched crop was also noted on the specified version of the experiment — 4.13 t/ ha, which is 2.58 t/ ha more than the control version.